2018
DOI: 10.1111/jicd.12332
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the effect of bisphosphonates during osteoporosis treatment on jawbones using multidetector computed tomography: The OSTEOSYR project

Abstract: The use of BP as a treatment for osteoporosis for 5 years increased the thickness of the cortex of the basal bone of the mandible, as detected by MDCT. The other parts of the jawbones showed no influence by BP for such a purpose, as detected on MDCT images. Accordingly, models (equations) for predicting the alternations in the inferior cortex of the mandible induced by BP therapy during osteoporosis have been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…As the corresponding average symptom durations were 4.5 and 3.2 months, respectively, MRONJ might have occurred 54 and 24 months after low-dose and high-dose antiresorptive therapy. This result was quite similar to the findings of previous studies, which reported that this condition developed 12 months after intravenous BP injection and > 3 years after oral BP therapy 20 , 21 . In another study, the prevalence of MRONJ was greater among patients with > 4 years of exposure to oral BPs than in those with shorter durations of exposure (0.21% vs. 0.04%).…”
Section: Discussionsupporting
confidence: 92%
“…As the corresponding average symptom durations were 4.5 and 3.2 months, respectively, MRONJ might have occurred 54 and 24 months after low-dose and high-dose antiresorptive therapy. This result was quite similar to the findings of previous studies, which reported that this condition developed 12 months after intravenous BP injection and > 3 years after oral BP therapy 20 , 21 . In another study, the prevalence of MRONJ was greater among patients with > 4 years of exposure to oral BPs than in those with shorter durations of exposure (0.21% vs. 0.04%).…”
Section: Discussionsupporting
confidence: 92%
“…Most of these studies reported that the cortical bone thickness of patients taking antiresorptive drugs was significantly greater than that of the control group. 5 7 10 11 12 13 However, other studies showed no significant difference between the 2 groups, 8 14 and 1 study 4 even reported that the cortical bone thickness of patients taking antiresorptive drugs was significantly smaller than that of the control group. However, because these studies were conducted in patients with osteoporosis, it is not clear whether the findings of thin cortical bone were due to osteoporosis or antiresorptive drugs.…”
Section: Are There Any Imaging Signs That Predict Mronj In Patients Tmentioning
confidence: 96%
“…Yajima et al 6 reported no significant difference between the cancellous bone mineral density (BMD) of a BP group and a non-BP group. They measured trabecular BMD using quantitative CT. Barngkgei and Khattab 7 investigated the effects of BP on the jaw bones using multidetector CT. They concluded that BP treatment for osteoporosis for 5 years showed no influence on the trabecular parts of the jaw bones.…”
Section: Are There Any Imaging Signs That Predict Mronj In Patients Tmentioning
confidence: 99%
“…While some investigations have utilized panoramic radiographs [12,14], the utilization of cone beam computed tomography (CBCT) images for this purpose in osteoporotic patients has been relatively uncommon. Existing CBCT studies have primarily focused on the mandibular cortical area [15,16], resulting in a gap in the comprehensive evaluation of broad-spectrum changes in this patient population. Therefore, the objective of this retrospective cohort study is to characterize the effects of ARDs on the maxilla and mandible and to identify risk factors for osteonecrosis development in osteoporotic patients undergoing tooth extractions, utilizing clinical data and CBCT assessment.…”
Section: Introductionmentioning
confidence: 99%